2005
DOI: 10.1065/espr2005.07.272
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Burning in the Amazon-Fertilizer for the Mountaineous Rain Forest in Ecuador (7 pp)

Abstract: The mountaineous rain forest in south Ecuador has developed on poor and acid soils, with low nutrient availability. The additional ferilization resulting from anthropogenic biomass burning constitutes a significant disturbance of this ecosystem, its functioning and biodiversity. Thus it is planned to employ isotope analyses for quantifying the pathways. of nitrate and sulfate deposition in these natural forests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 19 publications
2
49
0
Order By: Relevance
“…NUMEX was started in 2008 to study if and to what extent N and P limitation are controlling tropical montane forest functioning at three elevation levels (1000, 2000, and 3000 m) and to simulate the effects of future increasing nutrient availability from atmospheric deposition on different ecosystem processes. In southern Ecuador, nutrient deposition has been suggested to largely origin from extensive biomass burning occurring in the Amazon basin leading to increasing depositions of >10 kg N ha −1 in the last decade (Fabian et al, 2005;Wilcke et al, 2013). The continued nutrient addition in this experiment had already shown effects on various belowground to aboveground compartments in the experiment's first years: Homeier et al (2012) found in the common tree species a positive growth response after N (two out of four species), P (two out of four species) and N+P addition (three out of four species) and an increase of leaf litter production after N and NP addition suggesting that at 2000 m. a.s.l.…”
Section: Introductionmentioning
confidence: 99%
“…NUMEX was started in 2008 to study if and to what extent N and P limitation are controlling tropical montane forest functioning at three elevation levels (1000, 2000, and 3000 m) and to simulate the effects of future increasing nutrient availability from atmospheric deposition on different ecosystem processes. In southern Ecuador, nutrient deposition has been suggested to largely origin from extensive biomass burning occurring in the Amazon basin leading to increasing depositions of >10 kg N ha −1 in the last decade (Fabian et al, 2005;Wilcke et al, 2013). The continued nutrient addition in this experiment had already shown effects on various belowground to aboveground compartments in the experiment's first years: Homeier et al (2012) found in the common tree species a positive growth response after N (two out of four species), P (two out of four species) and N+P addition (three out of four species) and an increase of leaf litter production after N and NP addition suggesting that at 2000 m. a.s.l.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the mega-diverse tropical mountain rain forest in the southeastern Ecuadorian Andes (Bendix and Beck, 2009), biomass burning in the Amazon has been hitherto identified as the principal source of atmospheric sulfate deposition (Beiderwieden et al, 2005;Boy et al, 2008;Fabian et al, 2005Fabian et al, , 2009Rollenbeck et al, 2011). However, volcanic and biomass-burning emissions were included by roughly estimated data.…”
Section: Introductionmentioning
confidence: 99%
“…For this, Schemenauer and Cerceda (1994) found good agreements between the collection rates of different tree species and the standard fog collectors that we used in this study. For further details on field measurement techniques, calibration, and handling of the data, the reader is referred to Fabian et al (2005) and Rollenbeck et al (2007Rollenbeck et al ( , 2011. On the day of collection, electrical conductivity (WTW-LF 90) and pH (Methron 73065/682) of the samples were measured on site.…”
Section: Sulfate In Rain and Opmentioning
confidence: 99%
See 2 more Smart Citations